(3JfejI GdhYj HGdCef GdSjHQGfj HGdLGeYGJ GdeUQjI aj VhA GdNHQGJ GdYGdejI (B:s (3JUhQ ebJQM (B/s - (3,ESQGA eUWai fGUa aGRYs; (3OjfG MSf YHO GdTGajs; (3YHjQ CMeO cGYhgs (2024)
(3gOaJ gPg GdOQGSI Edi JYoqQa GdhYj HGdCef GdSjHQGfj HGdLGeYGJ, hJYoqQa NHQGJ GdLGeYGJ GdYGdejI aj JfejI GdhYj HGdCef GdSjHQGfj, hJYoqQa LghO GdLGeYGJ GdeUQjI aj JfejI GdhYj HGdCef GdSjHQGfj, hJYoqQa hGbY GdhYj HGdCef GdSjHQGfj dOj WdGH LGeYI GdbGgQI, hhVY JUhQ ebJQM dJfejI GdhYj HGdCef GdSjHQGfj(B. (3hGYJeOJ Ydi GdefgL GdhUaj, hGSJNOeJ GdGSJHGfI COGkI dLeY GdHjGfGJ(B. (3hJhUdJ Edi eLehYI ef GdfJGFL, ef CHQRgG eG jdj(B: (3OQLI hYj WdGH LGeYI GdbGgQI HGdCef GdSjHQGfj eJhSWI, hZjGH eQcR NGU HGdCef GdSjHQGfj HLGeYI GdbGgQI, hZjGH SjGSGJ hGVMI dOYe GdhYj HGdCef GdSjHQGfj HLGeYI GdbGgQI, hVYa CSGdjH GdJhYjI HGdCef GdSjHQGfj HLGeYI GdbGgQI, hbdI GdhYj HGdbhGfjf hGdJTQjYGJ GdeQJHWI HGdLQGFe GdSjHQGfjI, hVYa GdOYe GdeGOj GdebOe ddWdGH dehGLgI GdLQGFe GdSjHQGfjI(B.s
The study aimed to identify cybersecurity awareness in universities, Knowing the experiences of international universities in developing cybersecurity awareness, Knowing the efforts of Egyptian universities in developing cybersecurity awareness, Knowing the reality of cybersecurity awareness for Cairo University students, and develop a proposed visualization for developing cybersecurity awareness in Egyptian universities in light of the experiences of international universities. It relied on the descriptive approach, and used a questionnaire as a tool for collecting data. The study reached several results, the most important of which are: The degree of awareness of cybersecurity among Cairo University students is average, There is an absence of a special center for cybersecurity at Cairo University, There is an absence of clear policies to support cybersecurity awareness at Cairo University, Weak cybersecurity awareness methods at Cairo University, lack of awareness of the laws and legislation related to cybercrimes, weak financial support provided to students to confront cybercrimes.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024.s
(3HHdjhLQGajG(B: (3UaMGJ (B185-208.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3bVGjG SjGSGJ eYjfI aj GdJYdjes; (3GdhYjs -- (3GdCef GdSjHQGfjs -- (3GdLGeYGJ GdeUQjIs